Inverting Risk Assessment: Considering the Lowest Risk Clients in the Federal Criminal Justice System. (August 2019) - DeLisi, Matt; Elbert, Michael; Tahja, Katherine
More than 30% of federal defendants have no prior official criminal history other than their present offense, and despite the low-risk nature of a large group of federal defendants, more than nine out of every 10 serve time in prison. Because of the overincarceration of low-risk defendants, the high cost of incarceration, and other developing evidence, there is growing interest in federal jurisdictions to develop alternatives to incarceration for defendants who pose little risk to public safety. Using pilot data from 1, 046 federal pretrial defendants in a federal jurisdiction in the Midwestern United States, the current study developed a low-risk actuarial tool, validated the low-risk actuarial tool on a sample of pretrial candidates from the same federal jurisdiction, and examined recidivism outcomes at 1, 2, and 5 years after their entry into the pretrial phase of their federal prosecution. The assessment tool identified 65 clients as posing minimal risk, and these offenders accumulated just four arrests across 5 years. If all 65 defendants were sentenced to prison followed by supervised release, the total cost would be US$2.34 million, yet this blanket approach would have prevented just four arrests. The findings suggest two static criminal history factors coupled with age at onset of first offense and substance abuse predict excellent candidates for sentences of diversion and probation. Research implications and description of the development of the alternatives to incarceration screening work group in this jurisdiction are provided.